Husbandry and productivity of sheep and goats in the Sahel states of West Africa and in semi-arid Northeast Africa - Wilson, R.T. (1981)
Discussion of sheep and goat breeding in the Sahel states of West Africa and in semi-arid North East Africa. Topical discussions on the importance of sheep and goats in countries with semi-arid climates, major breeds and their aptitude for production, ownership patterns, management objectives of traditional owners in the semi-arid zone, contribution of sheep and goats to registered slaughtering and production parameters included.